(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2013)
An introduction to the meeting. Typical of Nora are the many layers, that testify the long life of the town. In the central area. The excavations of the Milan University have shown at least 7 urban phases, one on the other, each with own aspects. For this reason too, Nora was always an ideal stage for young archaeologists. Many of them show here the results of their researches.